Pengaruh Gaya Hidup Hedonisme, Visual Merchandising, dan Diskon Harga Terhadap Pembelian Impulsif di MR. DIY Plaza Medan Fair - Viktor Manurung; Hafiza Adlina; Onan Marakali Siregar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Developments in the world of retail business require companies to have good marketing strategies to face competition. Impulse buying is a consumer behavior that must be considered when marketing products. MR. DIY is a company operating in the retail industry. Companies in this industry have intense competition. This research aims to determine the influence of a hedonistic lifestyle, visual merchandising, and price discounts on MR impulse buying. DIY Plaza Medan Fair. The influence between hedonistic lifestyle, visual merchandising, and price discounts will be analyzed partially and simultaneously. This research uses quantitative methods with 96 consumers as research samples, with a sampling technique, namely purposive sampling. Data collection was carried out through a questionnaire using a Likert scale which was distributed to respondents directly at MR. DIY Plaza Medan Fair, while secondary data was obtained from literature study. Data analysis methods use validity tests, reliability tests, classical assumption tests, multiple linear analysis, and hypothesis testing with the help of SPSS. The results of the research show that the hedonistic lifestyle variable has a significant effect on impulse buying. Furthermore, the visual merchandising variable has a significant effect on impulse buying. And the price discount variable does not have a significant effect on impulse buying. The result of the determination test was that the correlation coefficient (R) was 0.58, which means that each variable, namely hedonistic lifestyle (X1), visual merchandising (X2), and price discounts (X3) were interconnected with purchasing decisions (Y) by 58%. This means that a hedonistic lifestyle, visual merchandising and price discounts have contributed to impulse buying..